Expressão diferencial do gene PBRM1 e sua qualificação clínica em tumores de próstata - Mota, Sara Teixeira Soares (2017)
Prostate cancer (PCa) is the sixth most common and most dominant cancer in the male population and the second largest cause of death after lung cancer. Defined as heterogeneous tumor, several mechanisms are involved with its onset and progression, especially those that alter the expression of different genes. Polybromo-1 (PBRM1/BAF180) protein is one of the subunits that gives specificity to the SWI / SNF chromatin remodeling complex and mutations within the PBRM1 domains are described in several types of cancers. However, its role in PCa has not been described yet. Using qPCR we evaluated the transcriptional levels of PBRM1 domains in the peripheral blood and tissue of patients with PCa and benign prostatic hyperplasia (BPH) and also in four cell lines, including a non-neoplastic (RWPE), a hormone responsive (LNCaP) and two hormones refractory (PC3 and DU145). Subsequently immunohistochemistry experiments were performed to evaluate the behavior of PBRM1 protein in patients with PCa. Western blotting and immunofluorescence assays confirmed and validated the protein expression profile in the cell compartments. PBRM1 domains were differentially expressed in PCa and BPH and in prostatic lines. BRD1 was able to distinguish cancer patients from those with benign disease, besides correlating with TNM. The protein was found in the nucleus, cytoplasm and membrane of patients with PCa. Higher expression in the nucleus was significantly when the PSA was ≥ 10ng / mL and in patients with a higher degree of Gleason as well. In the cell lines, PBRM1 was also found in different compartments and sizes. In RWPE the protein was full-length and in the nucleus, in LNCaP also full-lenght, but in the cytoplasm. In PC3 and DU145, it was located in the two compartments in a truncated form. PBRM1 may be involved in the development and progression of prostatic tumors, regulating different events associated with tumor biology. Given its role in modulating chromatin, defining mechanisms involved in its behavior may lead to new strategies for the treatment of PCa. Therefore, our results provide a basis for biologically significant and clinically relevant molecular genetic study. It is worth highlighting this is not only a study that aims the identification of biomarkers, but, mainly, it shows key events in the molecular understanding of PCa. Keywords: Prostate Cancer, PBRM1, differential expression, AR, remodeling complex